Introducation to Word 2010 - Conway, Pamela; Safari eBooks ([S.l.] : CompuWorks, 2012)
"This course covers the basic functions and features of Word 2010. After an introduction to Word's window components, students will learn how to use the Help system and navigate documents. Then they will enter and edit text, create and save documents, and learn how to enhance the appearance of a document by using various formatting options. They will also create tables, insert headers and footers, proof and print documents, and insert graphics."--Resource description page.
Title from title screen.
Publication information from resource description page (viewed Apr. 8, 2013).
Presenter, Pamela Conway.
Keywords: Word processing; Microsoft Word; Electronic books